SUSTAINABLE JOURNEYS IN KERALA: KERALA’S ECOTOURISM ENDEAVORS - 1. Beetu Sebastian , 2. Dr. Jenni K Alex (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Kerala, "God’s Own Country," is celebrated for its backwaters, beaches, forests, and hills. However, mass tourism threatens its fragile ecosystems. In response, Kerala has adopted ecotourism to balance conservation and development. By involving local communities, promoting environmental awareness, and encouraging responsible travel, ecotourism safeguards nature while boosting livelihoods. This study explores Kerala’s ecotourism initiatives, their socio-economic and ecological impacts, and the challenges they face. It also suggests strategies to strengthen sustainable tourism in the state.